Efficacy of chimeric antigen receptor T-cell therapy in testicular relapse of pediatric acute lymphoblastic leukemia: a multicenter retrospective study - Wang, Ning; Tang, Yanjing; Zhuang, Yong; Cai, Jiaoyang; Hu, Shaoyan; Yang, Xue; Fang, Yongjun; Wu, Xiaoyan; Wang, Ningling; Wang, Lingzhen; Zhai, Xiaowen; Yang, Minghua; et al. (Frontiers in Immunology, 2026)
IntroductionTesticular relapse constitutes one of the most frequent extramedullary recurrences in pediatric acute lymphoblastic leukemia (ALL), yet its clinical management remains incompletely characterized.MethodsThis study assessed treatment outcomes and long-term survival in children with testicular relapse following initial therapy under the CCCG-ALL-2015 study (ChiCTR-IPR-14005706, http://www.chictr.org.cn). In total, 66 patients from 13 medical centers were retrospectively analyzed. Clinical characteristics and survival outcomes were compared across salvage treatment modalities.ResultsThe median interval from initial diagnosis to testicular relapse was 37 months. Among 59 patients who received post-relapse therapy, the 2-year overall survival (OS) rate was 86.1% after a median follow-up of 33 months. Patients treated with chimeric antigen receptor T-cell (CAR-T) therapy showed a 2-year OS of 90.7%, compared to 81.7% in those managed with conventional regimens, such as chemotherapy, orchiectomy, or hematopoietic stem-cell transplantation (P > 0.05). Among 37 children with isolated testicular relapse, 18 underwent CAR-T therapy and 10 underwent orchiectomy, achieving 2-year OS rates of 92.3% and 100%, respectively (P > 0.05).DiscussionTesticular relapse typically emerged approximately 3 years after initial diagnosis. CAR-T therapy proved to be both safe and effective, providing survival comparable to conventional regimens and offering potential advantages in preserving life quality among long-term survivors.